2022
DOI: 10.3390/en15072491
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Pyrolysis of Brewer’s Spent Grain: Impact of Gas Atmosphere

Abstract: This work focuses on the impact of carrier gas on the quantity and quality of pyrolytic products received from intermediate pyrolysis of the brewer’s spent grain. In this study, three types of carrier gases were tested: argon, nitrogen, and carbon dioxide at three temperatures of 500, 600, and 700 °C. On the basis of the process conditions, the yield of products was determined. The ultimate analysis of the char was performed, and for selected chars, the combustion properties were determined. Gas chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The elemental composition of spent grain (carbon—46.8%, hydrogen—7.0%, oxygen—38.7%, nitrogen—0.7%, and sulphur—0.3%) does not meet the standards for fossil fuels [ 19 ]. Similar results of elemental analysis were obtained by other researchers [ 20 , 21 , 22 , 23 ], except for the amount of nitrogen, which was at the level of 3.46–5.45%. The discussed direction of spent grain use may not cover the total demand of the brewery for energy but it may be a stimulus for the introduction of a 100% renewable energy plan in a brewery.…”
Section: Literature Reviewsupporting
confidence: 90%
See 2 more Smart Citations
“…The elemental composition of spent grain (carbon—46.8%, hydrogen—7.0%, oxygen—38.7%, nitrogen—0.7%, and sulphur—0.3%) does not meet the standards for fossil fuels [ 19 ]. Similar results of elemental analysis were obtained by other researchers [ 20 , 21 , 22 , 23 ], except for the amount of nitrogen, which was at the level of 3.46–5.45%. The discussed direction of spent grain use may not cover the total demand of the brewery for energy but it may be a stimulus for the introduction of a 100% renewable energy plan in a brewery.…”
Section: Literature Reviewsupporting
confidence: 90%
“…13.6%). BSG analysed by Bieniek et al [ 23 ] contained lower amounts of fixed carbon—8.85%, and the samples tested by Coronado et al [ 20 ] contained bound carbon at the level of 17.48%. A high content of bound carbon and volatile substances increase the calorific value of all biomass fuels [ 19 , 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Bieniek, et al [39] researched the effect of biomass particle size on the yield of pyrolysis products. It was found that the small particles promoted cracking of the intermediates in the pyrolysis reaction, resulting in greater production of H2 and CO and less CO2.…”
Section: The Biofuels Production In the Pyrolysis Processesmentioning
confidence: 99%
“…A lack of landfills, environmental concerns, and public understanding all add to the concern about appropriate sustainable waste management. People are consuming more and producing vast amounts of garbage in order to reach higher living standards, and enterprises are expanding to accommodate these demands [1]. As a result, these unsustainable habits put additional strain on the ecosystem, which is already under stress, necessitating immediate action to undo the impact and safeguard the world for generations to come.…”
Section: Introductionmentioning
confidence: 99%